An Analysis of the Effect of Transformational Leadership on Employees Job Satisfaction and Employees Performance - Ronny Walean; Yeane Koyongian; Delli Sabudu (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
This study sought to examine the impact of transformational leadership on employee performance, as well as the impact of transformational leadership on job  satisfaction. Transformational Leadership that Influences Employee Performance in CV. Restu Mitra Manado. The research subjects are all CV. Restu Mitra Manado.employees. While The sample size is 50 employees from CV. Restu Mitra Manado, and the sampling method is convenience sampling. The convenience sampling and random sampling methods were used in this study. sampling technique Multiple linier regression analysis was used to examine the data. Other analyses include the classical assumption, hypothesis testing via the F test, and T-test, determination coefficient (R2) ) and Path Analysis. The study's findings revealed that transformational variables Leadership and job satisfaction have a significant influence, both individually and collectively.The Employee Efficiency Furthermore, the Transformational Leadership variables have a significant impact on Job Satisfaction. Leadership Transformation and Job Contentment Employees can explain 87.6 percent of performance and 12.4 percent of performance. be explained by variables not included in the model While the Path Analysis results show that the total effect outweighs the direct effect Job satisfaction was mentioned as an intervening variable with Transformational Leadership that has an impact on employee performance.Job Satisfaction; Transformational Leadership; Employee Performance